(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines Fitrat’s efforts to awaken the nation through his educational, literary, and social activities. As a leading figure of the Jadid movement, he promoted ideas aimed at raising public consciousness, developing modern education, and restoring national identity.